Bridging Cultural Divides: Psychometric Properties of the Urdu Adaptation of the Adult Temperament Questionnaire (ATQ-U) - Raheela Shahid; Dr. Abida Perveen; Dr. Nabeela Sulaiman (Review Journal of Social Psychology & Social Works, 2025)
Assessment is an essential aspect of evaluating the mental attributes of individuals. Assessment becomes fruitful when it best assesses, is subject-specific and culturally relevant, and gives significant outcomes. Thus, the current research formed an indigenous version of adult temperament assessment. To best assess and form a culture-specific assessment measure for Pakistani adults. This study aimed to translate and validate the English version of the Adult Temperament Questionnaire, short form (ATQ). It was translated into Urdu for use in Pakistan. Forward and backward translation was the adopted method for translating measuring instruments. Six bilingual experts were included in this process. To assess the psychometric properties of the translated Urdu version of the ATQ-U, it was administered to a random sample of 280 healthy male and female university students aged from 18 to 41 years old. The average age of the respondents was 22 (S.D = 5.36). Results indicate the Cronbach’s Alpha and McDonald's ω coefficients, significant inter-item, and inter-subscales correlations of four broad domains and related sub-scales of the ATQ-U, which ranges from .89 to .97, respectively. As well the statistical results aligned with the original ATQ scale results. Future studies aimed to conduct the translated Urdu version of the ATQ among the general population of different regions and provinces of Pakistan for greater generalizability and validity.